Time and Punishment: An Intertemporal Model of Crime - Davis, Michael L. (Journal of Political Economy, 1988)
If an increase in the rate at which a criminal commits crimes lowers the expected time until detection, the income from crime (net of expected fines) must be discounted at a rate that varies with the crime rate. This paper models the criminal's choice of the optimal crime rate under such conditions. It is shown that, irrespective of the criminal's attitude toward risk, an increase in the probability of detection is more likely to deter crime than a comparable increase in penalties. Other implications of the model for the optimal enforcement of laws are also explored.